PREFERRED MENSTRUAL HYGIENE PRACTICES AMONG ADOLESCENT GIRLS IN PRIMARY SCHOOLS, A CASE STUDY OF SELECTED PRIMARY SCHOOLS IN MBARARA CITY. - Asaasira, Ruth; Twinamatsiko, Medard; Komurere, Abigail (Student’s Journal of Health Research Africa, 2024)
This survey examined the preferred menstrual hygiene among adolescent girls in primary Schools. The purpose was to contribute towards the academic performance of female pupils since menstrual hygiene is perceived as key to their concentration and participation in class. The study population included female candidate pupils, school matrons, teachers, parents/guardians of female pupils enrolled in the candidate class, and other education technocrats like head teachers. The findings of the investigation revealed that sanitary towels are the most commonly used and effective menstrual hygiene practice. Regarding materials used to clean external genitalia, the findings revealed that most adolescent girls use clean water to clean themselves. For the storage of menstrual materials, the results of the study manifested that most adolescent girls store their menstrual hygiene in their suitcases while others store materials with school nurses and matrons. From the study findings, the present study recommends the use of disposable sanitary towels since they were found to give comfort to these adolescent female pupils. In addition, the government should improve access and affordability of sanitary towels since they have an impact on pupils’ academic performance. Also, school administrators should maintain and ensure the availability of clean water inside school premises. Lastly, there is a need to intensify health education among both girls and boys.